Claves para la definición de un paisaje cultural Arqueología, patrimonio, didáctica y turismo en la cuenca del Guadalquivir - Vaquerizo-Gil, Desiderio; Ruiz-Osuna, Ana (2023)
From its source in Sierra de Cazorla to its mouth in the Atlantic Ocean, the Guadalquivir River has been a feature of the identities of the communities settled around it throughout history. The resources provided by the river itself, its tributaries and its vast valley have contributed to the survival, well-being and development of different cultures. As a result of this relationship between people and terrain, various cultural landscapes have been created. However, the political, economic and health situation of recent years has threatened the sustainability of some of them, as well as its heritage, and in many cases they are condemned to abandonment and oblivion. The present monograph arose to reflect on this complex situation from multiple perspectives, including archaeology, the natural environment, didactics, new technologies and tourism. It is the result of collaboration by leading professionals and researchers from diverse academic fields. Together they aim to analyse various realities; to identify the heritage needs we face today; and to suggest proposals to (re)activate the cultural industries of the Guadalquivir Valley.